GENETIC IMPROVEMENT OF MICE AND WAYS TO CREATE NEW HYBRIDS - Yoldosheva Surayyo Qahramon kizi (Bright Mind Publishing, 2025)
Purpose–faith, man, knowledge, profession, spiritual and moral, common humanity, patriotism, beauty, faith, morality.
Keywords: Purpose–faith, man, knowledge, profession, spiritual and moral, common humanity, patriotism, beauty, faith, morality.